Do short messages service (SMS) increases the profitability of vegetable farmers? - Lamichhane, Jeevan; Timsina, Krishna Prasad; Bhusal, Yuba Raj; Adhikari, Surya Prasad; Subedi, Sanjiv (Nepal Agriculture Research Journal, 2025)
Timely unavailability of information can lead to inefficiencies in production, commercialization which in turn can affect farmers’ revenue and wellbeing. Nepal Agricultural Research Council sent short messages regularly on weekly basis and in case when the shocks arise. The objective of this study is to assess the impact of phone based short message service (SMS) on the profitability of the vegetable farmers. We conduct propensity score matching by taking 156 farmers who followed the SMS and 103 farmers as control for the study. We found average effect on the treatment on the profit of the vegetable farmers. Compared to the control group, treated farmers were also found to increase their knowledge attributes. Improvement over the existing SMS is needed for increasing the magnitude of the impact.